Analysis of Pitching Velocity in Major League Baseball Players Before and After Ulnar Collateral Ligament Reconstruction. (April 2014) - Jiang, Jimmy J.; Leland, J. Martin
Background: Ulnar collateral ligament (UCL) reconstructions are relatively common among professional pitchers in Major League Baseball (MLB). To the authors' knowledge, there has not been a study specifically analyzing pitching velocity after UCL surgery. These measurements were examined in a cohort of MLB pitchers before and after UCL reconstruction. Hypothesis: There is no significant loss in pitch velocity after UCL reconstruction in MLB pitchers. Study Design: Cohort study; Level of evidence, 3. Methods: Between the years 2008 to 2010, a total of 41 MLB pitchers were identified as players who underwent UCL reconstruction. Inclusion criteria for this study consisted of a minimum of 1 year of preinjury and 2 years of postinjury pitch velocity data. After implementing exclusion criteria, performance data were analyzed from 28 of the 41 pitchers over a minimum of 4 MLB seasons for each player. A pair-matched control group of pitchers who did not have a known UCL injury were analyzed for comparison. Results: Of the initial 41 players, 3 were excluded for revision UCL reconstruction. Eight of the 38 players who underwent primary UCL reconstruction did not return to pitching at the major league level, and 2 players who met the exclusion criteria were omitted, leaving data on 28 players available for final velocity analysis. The mean percentage change in the velocity of pitches thrown by players who underwent UCL reconstruction was not significantly different compared with that of players in the control group. The mean innings pitched was statistically different only for the year of injury and the first postinjury year. There were also no statistically significant differences between the 2 groups with regard to commonly used statistical performance measurements, including earned run average, batting average against, walks per 9 innings, strikeouts per 9 innings, and walks plus hits per inning pitched. Conclusion: There were no significant differences in pitch velocity and common performance measurements between players who returned to MLB after UCL reconstruction and pair-matched controls.